Research of the Transmission System of Pure Electric MPV with Two-speed Reducer - Yu Rui; Shi Weiqin; Ni Lanqing (Jixie chuandong)
According to the meaning and direction of automobile industry development,and the necessity of automobile electricization and the necessity of pure electric MPV（ Muti-purpose Vehicle） are expounded.According to the actual situation of China current industrial manufacturing industry,the MPV transmission system equipped with two-speed reducer is selected as the research object. In turn,the following work of parameters matching simulation of the transmission system,selection of the key parts of the system,trial production of the prototype and the debugging and experimental research are carried out. Furthermore,the experimental results show that the key components of the transmission system based on the simulation matching can perfectly meet the advanced requirements.